2007
DOI: 10.1038/nmeth1048
|View full text |Cite
|
Sign up to set email alerts
|

A semisynthetic epitope for kinase substrates

Abstract: The ubiquitous nature of protein phosphorylation makes it challenging to map kinase-substrate relationships, which is a necessary step toward defining signaling network architecture. To trace the activity of individual kinases, we developed a semisynthetic reaction scheme, which results in the affinity tagging of substrates of the kinase in question. First, a kinase, engineered to use a bio-orthogonal ATPgammaS analog, catalyzes thiophosphorylation of its direct substrates. Second, alkylation of thiophosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
306
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(309 citation statements)
references
References 30 publications
2
306
0
Order By: Relevance
“…We have recently reported a method for identification of askinase targets by using a monoclonal antibody that recognizes a chemically derivatized thiophosphorylation adduct (14,43). Although the antibody-based approach does not immediately identify the phosphorylation site targeted by an as-kinase, it is complementary to the method reported here because it leads to purification of the entire substrate protein.…”
Section: Many Phosphorylation Sites Identified Lack An Optimal Cdk Comentioning
confidence: 99%
“…We have recently reported a method for identification of askinase targets by using a monoclonal antibody that recognizes a chemically derivatized thiophosphorylation adduct (14,43). Although the antibody-based approach does not immediately identify the phosphorylation site targeted by an as-kinase, it is complementary to the method reported here because it leads to purification of the entire substrate protein.…”
Section: Many Phosphorylation Sites Identified Lack An Optimal Cdk Comentioning
confidence: 99%
“…An antibody was raised against the thiophosphorylhistidine derivative 2 but the antibody so raised could not distinguish pHis from other phosphoamino acids. 94,95 Pirrung et al 96 reported the preparation of malonate 3 and fluoromalonate 4 derivatives of His as τ-pHis analogues. However, no biochemical studies using these analogues have been reported.…”
Section: Phosphohistidine Analogues and Antibodiesmentioning
confidence: 99%
“…Here, we characterize thiophosphopeptide and thiophosphoprotein enrichment using iodoacetyl enrichment using both pH 4 and pH 8. Finally, we performed the enrichment using anti-thiophosphate ester antibodies, which were designed to purify the substrates of the analog-specific (AS) kinase (33). AS kinases can utilize N 6 -alkylated ATP-␥-S to produce thiophosphorylated substrates.…”
Section: Enrichment Of Thiophosphorylated Peptides Via Differentmentioning
confidence: 99%
“…The Shokat lab also developed an anti-thiophosphate ester antibody for specific kinase substrate purification (33). For this method to be effective, thiophosphopeptides are first alkylated using p-nitrobenzylmesylate (PNBM), producing a phosphoryl-conjugate that is then recognized by the antibody.…”
Section: Enrichment Of Thiophosphorylated Peptides Via Differentmentioning
confidence: 99%